Nekaj kontrastivnih beležk o italijanščini in slovenščini in nekaj opažanj o jezikovni produkciji pri govorcih slovenščine v Italiji - Ožbot, Martina (Jezik in slovstvo, 2009)
The paper presents some observations on systemic differences between Slovene and Italian which have been developed on the basis of the study of language production in students of Slovene, who mainly come from bilingual Slovene-Italian families. From early childhood, they have mostly been in very close contact with Slovene and at the same time with Italian. The latter is for many of them their primary language (at least for some communicative functions), which is also reflected in their use of Slovene. In addition to texts produced by students, the analysis includes texts by writers from the border region, in which various features can be found which are similar to those present in the texts written by students. Following from this analysis, the author singles out some contrastively relevant features of Italian and Slovene concerning aspects of grammar (punctuation, word order, pronouns, prepositions, the use of verb forms, etc.) and idiom, thus trying to sketch out a possible outline of an Italian-Slovene text grammar.
Keywords: Italian; Italija; italijanščina; Italy; primerjalne študije; Slovene; slovenščina; sociolinguistics; sociolingvistika; zamejski Slovenci